The pharmaceutical multi-activity of metallofullerenol invigorates cancer therapy. Issue 31 (31st July 2019) - Li, Jinxia; Chen, Linlin; Su, Haoran; Yan, Liang; Gu, Zhanjun; Chen, Zhaofang; Zhang, Aiping; Zhao, Feng; Zhao, Yuliang
Abstract : Multi-targeting Gd@C82 (OH)22 as a 'particulate medicine' against tumours. Abstract : Currently, cancer continues to afflict humanity. The direct destruction and killing of tumor cells by surgery, radiation and chemotherapy gives rise to many side effects and compromised efficacy. Encouragingly, the rapid development of nanotechnology offers attractive opportunities to revolutionize the current situation of cancer therapy. Metallofullerenol Gd@C82 (OH)22, in contrast to chemotherapeutics that directly kill tumor cells, demonstrates anti-tumor behavior with high efficiency and low toxicity by modulating the tumor microenvironment. Furthermore, Gd@C82 (OH)22 has been recently reported to specifically target cancer stem cells. In this review, we give a concise introduction to the development of the fullerene family and then report the anti-tumor activity of Gd@C82 (OH)22 based on its unique physicochemical characteristics, followed by a comprehensive summary of the anti-tumor biological mechanisms which target different components of the tumor microenvironment as well as the biodistribution and toxicity of Gd@C82 (OH)22 . Finally, we describe Gd@C82 (OH)22 as a "particulate medicine" to highlight its distinctions from conventional "molecular medicine", with considerable emphasis on the advantages of nanomedicine. The in-depth investigation of Gd@C82 (OH)22 undoubtedly provides a constructive reference for the development of other nanomedicines, especially in the fullerene family. The application of nanotechnology in the medical field definitely provides a promising and favorable future for improving the current status of cancer therapy.